180 The aorta can act as site of t cell priming and promotes a local cd4+ adaptive immune response in early stage atherosclerosis in apolipoprotein-e-/- mice. (5th June 2017) - MacRitchie, Neil; Grassia, Gianluca; Hughes, Catherine; Noonan, Jonathan; Schroeder, Juliane; Garside, Paul; Maffia, Pasquale
Abstract : Artery tertiary lymphoid organs (ATLOs) in the adventitia adjacent to intimal plaque in aortas from aged apolipoprotein-E (apoE) -/- mice have recently been shown by us to orchestrate the aortic immune response in the advanced stages of experimental atherosclerosis, highlighting the importance of the vascular immune response and its contribution to the pathology. Antigen presenting cells (APCs) and T cells are found in both human and animal naÃƒÂ¯ve and atherosclerotic vessels; however, the mechanisms leading to T cell activation in the arterial wall remain poorly understood. Here we utilised flow cytometry to present a quantitative assessment of the major antigen presenting cells in both C57BL/6 wild type (WT) and apoE -/- mice in the aorta, aortic draining lymph nodes and spleen. By employing a model antigen and antibody detections system (Eα-GFP/Y-Ae), it was possible to assess the ability of aortic APC subsets to present antigen in vivo . We also performed a comprehensive phenotypic analysis of CD4 + T cells in healthy versus atherosclerotic aorta using surface marker expression and cytokine signatures. This study revealed that aortas from atherosclerotic mice contained more CD4 + T cells and more Th1 T cells (IFN-γ³+) compared to WT, as well as showing a phenotypic switch from a nave to an activated phenotype. On the contrary, changes in T cell phenotype in the spleen and draining lymph nodes between WT and apoE -/- mice were either equivalent or modest. One hypothesis regarding the presence of T cell autoreactive clones in the atherosclerotic vessel is that CD4 + T cells are activated locally in the vessel by plaque derived antigens. To determine if T cell priming can occur locally in the aorta, we first identified nave T cells in the aorta of WT and OT-II mice (transgenic mice with CD4 + T cells with a TCR specific for chicken ovalbumin 323–339 peptide in the context of I-A b ) and then challenged OT-II mice with ovalbumin while blocking lymphocyte trafficking/egress and extravasation. These experiments revealed that nave T cells could not only be primed directly in the vessel wall but that the kinetics and respective magnitude of T cell proliferation to antigen was comparable with aortic draining lymph nodes and spleen, supporting a role for the vessel as a seat of T cell priming. Together this data illustrates that the aorta can support antigen presentation and that CD4 + T cells in the atherosclerotic aorta develop a more activated phenotype associated with Th1 cytokine expression, cytokines known for promoting macrophage activation and plaque instability. Most importantly, we demonstrate that the aorta has the capacity to mimic lymphoid tissue in being able to support local antigen driven proliferation of CD4 + T cells.